Acute uncomplicated diverticulitis managed without antibiotics – difficult to introduce a new treatment protocol but few complications. (2nd January 2019) - Azhar, Najia; Kulstad, Hanna; Pålsson, Birger; Kurt Schultz, Johannes; Lydrup, Marie-Louise; Buchwald, Pamela
Abstract: Objective: Routine antibiotic treatment of acute uncomplicated diverticulitis (AUD) has been shown ineffective. In this study, the adherence to a new treatment protocol for uncomplicated diverticulitis was evaluated and the incidence of complications in patients treated with and without antibiotics was investigated. Materials and methods: A retrospective study of in-patients diagnosed with AUD at Helsingborg Hospital, Sweden between 01 January 2013 and 06 January 2015 was performed. Antibiotics were routinely administrated until 01 May 2014. Thereafter, a new antibiotic-free treatment protocol for uncomplicated diverticulitis was introduced. All the patients were followed regarding complications for minimum one year. Results: A total of 50 patients were studied after the new protocol implementation and, 60% ( n  = 31) of the patients were treated without antibiotics. Specialists initiated antibiotic therapy significantly more often than registrars ( p =.03). More patients in the antibiotic group had comorbidities ( p =.03), apart from that, no significant differences in baseline characteristics were noted between treatment groups. Patients treated with antibiotics after introduction of the new protocol had significantly higher C-reactive protein than patients managed without antibiotics (median 117 mg/L vs. 70, p =.005). The hospital stay was shorter in the non-antibiotic group (three days vs. two days; p =.008). No significant differences in complications were observed. Conclusions: Protocol compliance was lower than expected, indicating that implementation of new treatment regimens is challenging. This study confirms that complications are rare in AUD treated without antibiotics. However, the selection of the sickest patients to the treatment with antibiotics limits the interpretation of the results.